Type 1 Diabetes - Escher, Alan P.; Li, Alice (IntechOpen, 2013)
This book contains a series of up-to-date chapters that review our current knowledge of type 1 diabetes as an autoimmune disease, the problems that still remain with existing treatments, and possible solutions for the near future.